CHEMICAL ANALYSIS OF OIL AS PART OF MARKETING ESSENTIAL OIL CROPS E.G. PELARGONIUM VAR ROSE - Swanepoel, K. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
There is an increasing world demand for the high quality rose geranium essential oil of Pelargonium species which contains geraniol, linalool and citronellol. It is mainly used as, substitutes for the expensive attar of roses in the perfume & flavouring industry and to treat cellulite. The price depends on the quality of the oil and the specific market it is suitable for. If the quality is unknown to the producer, the market is unsure, and the producer may be exploited. The aim was to determine the maximum yield and quality for this cultivar in line with the market requirements. This information and technology is transferred to emerging farmers. The results were obtained from trials and commercial farmers in Mpumlanga, KwaZulu Natal, Eastern and Western Cape as well as small farmers in Gauteng. Chemical analysis of different harvests, were compiled into a collective data base. This can be seen as a sign of the growing industry of essential oils in South Africa by commercial and emerging farmers. Improved agricultural practices and the chemical analysis could make a difference in the marketability of geranium into different markets